The Analysis of Lily Bloom’s Trauma in Colleen Hoover’s it Ends with Us - Sarungu, Lidya G.; Andayani, Ambar (Austronesian: Journal of Language Science & Literature, 2025)
This study investigates the representation of trauma in Colleen Hoover’s It Ends with Us through the experiences of the main character, Lily Bloom. The objective is to identify how Lily’s trauma is reflected, its causes, its effects, and the coping mechanisms she employs. A psychological approach is applied, drawing on the theories of Cathy Caruth, Judith Herman, and James Pennebaker, with descriptive qualitative analysis used to examine textual evidence from the novel. The findings show that Lily’s trauma is reflected in repetitive behaviors such as shuffling cards and in dissociative experiences like hallucinations. The primary cause of her trauma is her father’s domestic violence, while its effects include difficulties in relationships, emotional conflict, and instability, but also resilience and post-traumatic growth. Expressive writing functions as her main coping strategy, helping her process painful memories and ultimately break the cycle of abuse. This study concludes that It Ends with Us portrays the psychological complexity of trauma and emphasizes the role of literature in representing recovery. The research contributes to trauma studies and literary analysis by demonstrating how fiction can reveal the lived realities of trauma survivors and provide insight into pathways of healing.